2017
DOI: 10.1016/j.heares.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Spectro-temporal cues enhance modulation sensitivity in cochlear implant users

Abstract: Although speech understanding is highly variable amongst cochlear implants (CIs) subjects, the remarkably high speech recognition performance of many CI users is unexpected and not well understood. Numerous factors, including neural health and degradation of the spectral information in the speech signal of CIs, likely contribute to speech understanding. We studied the ability to use spectro-temporal modulations, which may be critical for speech understanding and discrimination, and hypothesize that CI users ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 65 publications
(86 reference statements)
2
23
0
Order By: Relevance
“…354–5664 Hz) 15 . STM stimuli have been used for assessing psychoacoustic capabilities in recent studies 31 , 32 . …”
Section: Methodsmentioning
confidence: 99%
“…354–5664 Hz) 15 . STM stimuli have been used for assessing psychoacoustic capabilities in recent studies 31 , 32 . …”
Section: Methodsmentioning
confidence: 99%
“…Won et al (2015) did not find any strong evidence that spectrotemporal modulation detection, that is, the minimum modulation depth required to detect the STM, was correlated with either the subjects' ability to detect AM or static spectral ripples. Zheng et al (2017) also reported that the spectrotemporal modulation transfer functions cannot be predicted by the temporal, or spectral modulation transfer functions. In fact, the spectral transfer function, decomposed from a spectrotemporal modulation transfer function, was better than the measured values, especially for stimuli with higher ripple density.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) did not find any strong evidence that spectrotemporal modulation detection, that is, the minimum modulation depth required to detect the STM, was correlated with either the subjects’ ability to detect AM or static spectral ripples. Zheng et al. (2017) also reported that the spectrotemporal modulation transfer functions cannot be predicted by the temporal, or spectral modulation transfer functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, STMD paradigms have been used to explore perceptual learning mechanisms in the auditory system (Sabin et al, 2012). SMD/STMD tests have also used spectral/spectrotemporal resolution successfully as an outcome measure in different fields of audiological research: prediction of speech understanding in noise of hearing-aid users (Bernstein et al, 2016), assessment of cochlear implant candidacy, parameter fitting, and new sound processing strategies (Langner et al, 2017;Choi et al, 2016;Croghan and Smith, 2018;Zheng et al, 2017), evaluation of bimodal hearing benefit (Zhang et al, 2013), and music perception (Choi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%